Manual on rice genetic resources conservation and genebank management - Borromeo, Teresita H. (Philippine Rice Research Institute, 1994)
Standard operating procedures of genetic resources conservation and management are outlined in this guide. Procedures on collection, characterization, seed processing and documentation are thoroughly discussed in this manual. This manual is designed to serve as a guide for rice genebank personnel and researchers involved or interested in rice genetic resource conservation and management activities especially on the collection of traditional varieties and wild species. The procedures allow the maintenance and conservation of the genetic identity of all accessions. Leading Authorities on rice genetic resources published this book, namely, University of the Philippines Los Banos and the Philippine Rice Research Institute.